Predicted and observed impacts of COVID-19 lockdowns: two Health Impact Assessments in Scotland and Wales. (11th November 2022) - Green, Liz; Ashton, Kathryn; Bellis, Mark; Clements, Timo; Douglas, Margaret
Abstract: Health Impact Assessment is a key approach used internationally to identify positive or negative impacts of policies, plans and proposals on health and well-being. In 2020, HIAs were undertaken in Scotland and Wales to identify the potential health and well-being impacts of the 'stay at home' and physical distancing measures implemented at the start of the coronavirus disease (COVID-19) pandemic. There is sparse evidence evaluating whether the impacts predicted in HIAs occur following policy implementation. This paper evaluates the impacts anticipated in the COVID-19 HIAs against actual observed trends. The processes undertaken were compared and predicted impacts were tabulated by population groups and main determinants of health. Routine data and literature evidence were collated to compare predicted and observed impacts. Nearly all health impacts anticipated in both HIAs have occurred in the direction predicted. There have been significant adverse impacts through multiple direct and indirect pathways including loss of income, social isolation, disruption to education and services, and psychosocial effects. This research demonstrates the value of prediction in impact assessment and fills a gap in the literature by comparing the predicted impacts identified within the HIAs with observed trends. Post-COVID-19 recovery should centre health and well-being within future policies and decisions. Processes like HIA can support this as part of a 'health in all policies' approach to improve the health and well-being of populations. Lay Summary: Health Impact Assessment (HIA) is an approach used to identify positive or negative impacts of policies, plans and proposals on health and well-being. In 2020, HIAs were undertaken in Scotland and Wales to identify the potential health and well-being impacts of the 'stay at home' and physical distancing measures (commonly called 'lockdown') which were put in place at the start of the COVID-19 pandemic. This paper evaluates whether these assessments were correct in their predictions. It finds that most of the health impacts anticipated in both assessments have occurred. These include significant impacts on income, employment and mental health. Using HIAs can help policymakers to take full account of these wider impacts on health and develop policies that benefit health and health equity.